HUBUNGAN UMUR, PENDIDIKAN, DAN PENGETAHUAN IBU DENGAN UPAYA MEMPERSIAPKAN MASA PUBERTAS PADA REMAJA DI RT 48 KELURAHAN 3-4 ULU PALEMBANG TAHUN 2018 - Adelina Pratiwi (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2019)
Adolescent problems related to reproductive health risk occur due to various changes around the environment of adolescents, such as peer group lifestyles that are increasingly free, the relationship of life in the family is increasingly tenuous, the demands of schools that increasingly give rise to competition between students and students, the content of mass media messages is increasingly permissible, as well as the pattern of community life that is increasingly individualized. The lack of preparation for children facing puberty is a serious psychological hazard. This study aims to determine the relationship between mother?s age, education and knowledge with efforts to prepare for puberty in adolescents in RT 48 Kelurahan 3-4 Ulu Palembang in 2018. This research method uses analytical survey with Cross Sectional approac . Sampling is done by non random sampling technique with a population of 111 family heads and sample 32 respondents. The results of research on the variables of mother?s age, education, and knowledge of each have a relationship with efforts to prepare for puberty in children with pvalue of 0.030 <? 0.05 for mother?s age, pvalue 0.014 <? 0.05 for education, and pvalue 0.002 < ? 0, 05 for knowledge. The researcher hopes that health workers, especially midwives, will provide more counseling or open counseling to every woman who comes to the posyandu in RT 48 Kelurahan 3-4 Ulu, so that she can get information about the benefits and importance of efforts in preparing for puberty in children.